A new inhight on the Portuguese traditional sweets as cultural identity: a scientific approach towards evaluation of texture in Castanhas de Ovos de Viseu - Guiné, Raquel (2016)
The importance of the gastronomic heritage of any people is unquestionable and Portugal is particularly rich when it comes to sweets. Hence, the objective of this work was to give a contribution colour and texture, due to their importance for consumer acceptance. The samples were bought from a pastry in Viseu and produced according to the traditional recipe. Colour evaluation was made by a colorimeter and textural analysis by a texturometer. The results obtained allowed concluding that there were differences between the top burned area and the non-burned areas, as well as when comparing the ruffled with unruffled samples either regarding colour and also texture. The burned area was darker, with a more intense red and less yellow. As to texture, the ruffles samples were harder than the unruffled samples.